2016
DOI: 10.1016/j.jneumeth.2016.08.003
|View full text |Cite|
|
Sign up to set email alerts
|

Animal models of resistance exercise and their application to neuroscience research

Abstract: Background Numerous studies have demonstrated that participation in regular resistance exercise (e.g., strength training) is associated with improvements in mental health, memory, and cognition. However, less is known about the neurobiological mechanisms mediating these effects. The goal of this mini-review is to describe and evaluate the available animal models of resistance exercise that may prove useful for examining CNS activity. New Method Various models have been developed to examine resistance exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 108 publications
(145 reference statements)
0
21
0
2
Order By: Relevance
“…Further support is seen in a recent study in young adult female rats that showed that combined AT and RT enhanced spatial learning and memory in the Morris water maze and conditioned avoidance memory compared to controls, and performance correlated with increases in hippocampal neurogenesis [128]. However, it is important to note that most current in vivo rodent models of RT employ significant aerobic components in their protocols [36], thus limiting their ability to disentangle the mechanisms underlying AT versus RT.…”
Section: Type Of Exercise Is An Important Moderatormentioning
confidence: 96%
“…Further support is seen in a recent study in young adult female rats that showed that combined AT and RT enhanced spatial learning and memory in the Morris water maze and conditioned avoidance memory compared to controls, and performance correlated with increases in hippocampal neurogenesis [128]. However, it is important to note that most current in vivo rodent models of RT employ significant aerobic components in their protocols [36], thus limiting their ability to disentangle the mechanisms underlying AT versus RT.…”
Section: Type Of Exercise Is An Important Moderatormentioning
confidence: 96%
“…The positive impact of physical exercise on many aspects of human health is well established (Mammen & Faulkner;2013). Not only aerobic exercise (Strickland & Smith, 2016) but also resistance exercise (Cassilhas et al 2007;Liu-Ambrose et al 2010) has been reported to have beneficial neurobiological effects in animals and humans. In humans, resistance exercise confers cognitive and mental health benefits (Cassilhas et al 2007;O'Connor et al 2010).…”
Section: Beasmentioning
confidence: 99%
“…On the other hand, resistance training for rodents has always been a reason for debate (Cholewa et al., 2013; Krause Neto, Silva, Ciena, Anaruma, & Gama, 2016; Strickland & Smith, 2016). Such controversy was generated from the apparent differences found between the equipment used for the training of rodents and humans.…”
Section: Introductionmentioning
confidence: 99%